STRATEGIC HUMAN RESOURCE OPTIMIZATION IN BUSINESSMANAGEMENT AMIDST THE TECHNOLOGICAL EPOCH FOR ADVANCING PROFITABILITY AND SUSTAINABILITY IN INDONESIA - Albert Budiyanto; A. Hamid; Muhammad Syafri; A. Haris Mzen; Mohammad Aldrin Akbar (CV. Adiba Aisha Amira, 2024)
In the study